ROLE OF THE FRACTION’S HYDRAULIC SIZE IN SEDIMENTS COMPOSITION FORMING - TIULIENIEVA, N.; KADURIN, S.; SUCHKOV, I.; FEDORONCHUK, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The hydraulic size of psammite, aleurite, pelite fractions, and some of heavy fraction’s minerals form recent liman and marine sediments is calculated, within Dniepro-Bugsky liman, submarine part of Kinburnsky spit and Yagorlytsky bay (north-west shelf of the Black Sea). On basis of study of hydraulic size the sediments forming model is built. Presented model is the basis for more difficult model, where greater number of factors will be taken into account.